Age and Sex Modulate Albumin, Glomerular Filtration Rate, and Lipid Profile in Type 2 Diabetic Patients - Aphrodite Tchewonpi Choumessi; Brice Ulrich Foudjou Saha; Tafrie Yuefebop; Junior Kum Tegha Muankang; Faustin Pascal Tsague Manfo; Edouard Akono Nantia (Al-Anbar Medical Journal)
Background: Metabolic factors associated with type 2 diabetes mellitus (T2DM) remain poorly understood, especially in the context of population-specific influences and varying environmental settings.Objectives: To investigate the modulation of albumin, lipid profile biomarkers, and glomerular filtration rate (eGFR) in T2DM patients attending the Bamenda Regional Hospital in Cameroon.Materials and Methods: Briefly, 153 patients were interviewed on their socio-demographic and anthropometric information, and their fasting blood glucose (FBG) level, lipid profile, albumin, and eGFR were determined.Results: The majority (61.4%) of participants were females and almost half (45.7%) of the population was obese. The FBG level was lower in the older age group (70-79 years, 165.62±17.95 mg/dL) than those moderately younger (≤69 years, 241.26±12.96 mg/dL). Also, the eGFR (65.97±4.03 ml/min/1.73m2) and high-density lipoprotein (HDL) level (54.06±2.84 mg/dL) decreased in older patients, particularly in the age 70-79 years. Male participants had higher albumin levels than the females (4.77±0.12 g/dL vs. 4.38±0.11 g/dL). Moreover, albumin was higher in the younger population (39-49 years; 4.99±0.22g/dL) as compared to older individuals (80-89 years; 4.07±0.22 g/dL). Correlation analyses revealed significant associations of FBG, albumin, eGFR, triglycerides, HDL, and low-density lipoprotein with age, gender, and body mass index.Conclusion: The findings suggested significant variations in albumin, lipid biomarkers, and eGFR among diabetic patients, with age, gender, and cholesterol levels being the key modulators. Older patients seem particularly affected, making them a critical group for targeted management of T2DM.